MACROBITS, a teaching tool for quantum cryptography (Revista do Professor de Física, 2022)
One amazing characteristic of quantum algorithms is how they can deliver results with 100% certainty despite their structure being based on the probabilistic interpretation of quantum mechanics. This type of algorithm requires a different way of thinking and sets a challenge for science educators. A routine to emulate quantum cryptography protocols for high school students is proposed in this work. The educational procedure uses a tool we have developed and called MACROBIT as a mean to mimic algorithms of quantum key distribution. The MACROBITS are useful to illustrate quantum mechanics concepts such as superposition, change of basis and quantum measurement.